2017
DOI: 10.36076/ppj.2017.1.e199
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on Red Ear Syndrome with Tinnitus Successfully Treated with Transcranial Random Noise Stimulation

Abstract: Background: The red ear syndrome represents a rare symptom complex consisting of auricular erythema associated with painful and burning sensations. It has been described in combination with tinnitus rarely. It has been hypothesized to be etiologically related to altered trigeminal afferent input, temporomandibular disorders, and thalamic dysfunction. Objectives: The initial objective of applying transcranial random noise stimulation (tRNS) in a case of red ear syndrome in combination with tinnitus was the alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Our findings are in line with earlier studies, which demonstrated that tinnitus severity is higher in patients with comorbid headache ( 24 ) and correlates with headache frequency ( 25 ). A potential interaction between tinnitus and migraine ( 26 30 ) or other trigeminoautonomal headache syndromes ( 31 , 32 ) has been described in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with earlier studies, which demonstrated that tinnitus severity is higher in patients with comorbid headache ( 24 ) and correlates with headache frequency ( 25 ). A potential interaction between tinnitus and migraine ( 26 30 ) or other trigeminoautonomal headache syndromes ( 31 , 32 ) has been described in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the direction of electrode polarization is critical in terms of the after-effects. Through stimulation of the motor cortex, tDCS can be used for: chronic pain (Deer et al 2014;Souto et al 2014;Hodaj et al 2016), pain after endoscopic retrograde cholangiopancreatography (Borckardt et al 2011), trigeminal pain including refractory orofacial pain (Antal et al 2010;Hansen et al 2011;DosSantos et al 2012;Hagenacker et al 2014;Fricova et al 2016;Kreuzer et al 2017), fibromyalgia (Valle et al 2010;Cummiford et al 2016;Castillo-Saavedra et al 2018), major depression (Vigod et al 2014;Tortella et al 2015;Brunoni et al 2016;Liu et al 2017), bipolar disorder (Bersani et al 2015;Pereira-Junior et al 2015;Tortella et al 2015), schizophrenia (Agarwal et al 2013;Palm et al 2016;Gögler et al 2017), Alzheimer's disease (Nardone et al 2012;Bystad et al 2016;Narita and Yokoi 2017), modulation of associative learning (Branscheidt et al 2017), Parkinson's disease (Benninger et al 2010;Hendy et al 2016;Schabrun et al 2016), pain after stroke (Schjetnan et al 2013;Chhatbar et al 2016;Russo et al 2017) and tinnitus (Garin et al 2011;…”
Section: Nibs: Transcranial Electrical Stimulationmentioning
confidence: 99%
“…This problem does not occur when tACS is used in the "ripple" frequency range (Moliadze et al 2010). Ripples Kringelbach et al 2007;Pereira et al 2007Pereira et al , 2013Holslag 2018;Johnson et al 2008 Strong Holtzheimer and McDonald 2014;McNamara et al 2001;George and Belmaker 2007;Prikryl et al 2013;Fregni et al 2005;Ferreri et al 2003;Li et al 2013;Politi et al 2008;Shen et al 2016Shen et al , 2017 Non-invasive Low spatial targeting compared to DBS, higher cost compared to other non-invasive methods rTMS pain Rokyta and Fricová 2012;Fricová et al 2013;Kohútová et al 2017;Robertson et al 2010;Thomas et al 2007, Shupak et al 2006Thomas et al 2001 Non-invasive, low cost Less pronounced effect compared to rTMS tDCS chronic pain, trigeminal pain including refractory orofacial pain, fibromyalgia, major depression, bipolar disorder, schizophrenia, Alzheimer's disease associative learning, Parkinson's disease, pain after stroke, tinnitus Souto et al 2014;Hodaj et al 2016;Borckardt et al 2011;Antal et al 2010;Hansen et al 2011;DosSantos et al 2012;Hagenacker et al 2014;Kreuzer et al 2017;Fricova et al 2016;Castillo-Saavedra et al 2018;Valle et al 2010;Tortella et al 2015;…”
Section: Nibs: Transcranial Electrical Stimulationmentioning
confidence: 99%
“…hf- tRNS has also been found to be able to enhance mathematical ability speed 11 and perceptual learning 5 . In a case report the successful treatment of a patient suffering from “Red Ear Syndrome” by high-frequency tRNS was registered 12 . The “Red Ear Syndrome” contains a symptom complex of auricular erythema, attack-like local pain and tinnitus perception 13 .…”
Section: Introductionmentioning
confidence: 99%